POLA PENGASUHAN ANAK PADA KELUARGA NELAYAN DI DESA BOEDINGI KECAMATAN LASOLO KEPULAUAN KABUPATEN KONAWE UTARA - Latif, Abd. Hadide; Jamiludin, Jamiludin; Basri, La Ode Ali (Jurnal Wahana Kajian Pendidikan IPS, 2018)
Abstract: Title Patterns of Parenting for the Family of Fishermen in the Village of Boedingi District of Lasolo Islands of North Konawe Regency. Objectives: (1). To describe the pattern of parenting performed by the father and mother in raising children to fishing families in the village of Boedingi Kecamatn Lasolo Islands District of North Konawe. (2). To describe the division of roles performed between father and mother in the village of Boedingi District of Lasolo Islands of North Konawe Regency. (3). To describe the constraints faced by fishermen families in raising children in the village of Boedingi, District of Lasolo Islands of North Konawe Regency. In this research the method used is qualitative method. Data collection methods used are: interviews, observation, and documentation. The research focus used are: Parents who have children who are domiciled in Boedingi Village, Lasolo District of Kabuaten Island, North Konawe. The data sources used are: primary data and secondary data. Data collection techniques used in this study are: Observation, interviews, and document studies. Data analysis techniques used descriptive qualitative data analysis consisting of four stages: data collection, data reduction, data presentation, and conclusion (verification). The results in this study indicate that (1). The pattern of democratic care is characterized by the encouragement of parents for children and always pay attention to the education of their children. However, sometimes parents apply these three types of parenting like authoritarian methods of care, and permissive nurture patterns depend on the situation and conditions experienced by parents to their children. (2). Division of roles between father and mother in fishing family in Boedingi Village, Lasolo sub-district of North Konawe Islands where most of the child-related tasks are assigned to mothers. Starting from attention to the needs of children such as eating and drinking, cooking, accompany learning, accompany play, accompany child sleep, instill norms in behaving and behaving, healthy lifestyle, attention to the needs of children, has become a routine task mother. (3) The constraints faced by the families of fishermen in the care of children are the lack of time available for parenting due to the busyness experienced by parents in the fishermen's family.Keywords: Patterns of Parenting Family of Fishermen, Division Role of Fisherman's Family, and Constraints it faces.